Malaysia’s Warm Weather as a Metaphor - Wen Fen Beh; Florence Kuek (PORTAL: Journal of Multidisciplinary International Studies)
Conveying one’s sense of belonging to a country can be challenging. Often, it is expressed in a rather cliché, impersonalised manner. However, the clever use of imagery could evoke relatable, authentic and lasting impressions. Borrowing from a local Chinese folk song genre, Tan & Teoh (2006)’s “Yong Malaixiya de Tianqi Shuo Ai Ni (Let Me Use Malaysia’s Warm Weather To Say, I Love You)” carries immense love for their native land using an apt metaphor of the “warm” Malaysian weather. Located on the Equator, Malaysia experiences high temperatures all year round. Malaysian hospitality is likened to its weather, and this admirable quality is apparent in the way of life of Malaysians, the country’s culture and traditions. Unable to exploit the vibrant or changing seasonal colours of temperate countries, Malaysian songwriters use this endearing weather metaphor to call attention to its warmth, serenading readers with a unique romance and catchy refrain.